Taxonomic notes on the Protohermes changninganus species group (Megaloptera: Corydalidae), with description of two new species - Liu, Xingyue; Hayashi, Fumio; Yang, Ding (Zootaxa, 2013)
Species of the dobsonfly Protohermes changninganus group are revised. Protohermes curvicornis sp. nov. and P. ohli sp. nov. are herein described and placed in the P. changninganus group. Protohermes tengchongensis Yang & Yang is considered a junior subjective synonym of P. subnubilus Kimmins.